Faktor-Faktor Yang Mempengaruhi Behavior Intention Terhadap Penggunaan Digital Payment : Systematic Literature Review - Ayem, Sri; Cahyaning, Enggar Kartika; Ramadhan, Idris; Nurlitawati, Merna; Langkodi, Hiskia; Trasno, Filynsia Amelia (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The increasing technological advances in the era of the Industrial Revolution 4.0 have led to a transfiguration of customer attitudes towards the use of digital technology and almost every aspect of life has been digitized, including non-cash payments or commonly referred to as digital payments. This research intends to identify and analyze the influence of the UTAUT model on Behavior Intention when using digital payments. This research uses a systematic literature review technique or a review of previous research for the 4 main aspects of the UTAUT model, namely FE, EE, SI, and FC, to determine whether it affects the behavior of using digital payments. In this study, using secondary data from article journeys starting from 2019-2023 from Publish or Perish. The results showed that Performance Expectancy (FE), Effort Expectancy (EE), Social Influence (SI), and Facilitating Conditions (FC) affect behavioral intentions when using digital payments. The results of the study are expected to be a reference and source of information regarding factors that can influence Behavior Intention when using digital payments.